The Evolution of Women’s Representation in Indonesian Film: A Narrative Review - Ambar Alimatur Rosyidah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The representation of women as the main characters in the film has a significant inequality with the male characters. Women are often portrayed as passive characters and become sexually objectified. The portrayal is inseparable from the patriarchal culture that has taken root in Indonesia. This kind of representation will affect how women, especially teenagers, think, identify, and make decisions. The purpose of this study is to examine the evolution of women’s representation in Indonesian films across the Old Order, New Order, and contemporary periods. Materials and methods. The author used a narrative review research design, which allows describing what is known about a topic while conducting a subjective examination and critique of the entire literature. This type aims to identify and summarize previously published articles, avoid duplication of research, and explore new, under-researched areas of study. Results. The findings in this study are three phases of film development in Indonesia, namely the Old Order phase (1950-1965), where women are underrepresented; the New Order phase (1966-1998), where we would find commodification of women's sensuality; and the Contemporary phase (1998-present), where women are trying to cope with the patriarchal culture. Conclusions. Feminist ideology in films has emerged since the fall of the Soeharto regime, showcasing a diverse range of female characters and their struggles against patriarchal culture. However, the film industry remains male-dominated, and the lack of women behind the scenes certainly impacts how women’s voices are heard.